The Effect of Early Mobilization on Intestinal Peristaltics in Patients after a Cesarean Section in Kendari City Hospital - Andi Herman; Budi Santoso; Esty Yunitasari (Jurnal Ners, 2019)
Background: Cesarean section (CS) is the most significant surgical intervention that affects the central nervous system and that slows down the bowel movement after CS. Intervention in the early period after CS is needed to improve bowel function. This study aims to determine the effect of early mobilization on intestinal peristalsis after cesarean section.Method: This quasi-experimental study was conducted on 72 patients divided into two groups of 36 for the intervention group at Dewi Sartika Public Hospital and for the control group at Kendari Public Hospital. A paired T-test was used for the data analysis.Result: After the intervention, there was a significant improvement in intestinal peristalsis in the intervention group (P<0,05).Conclusion: Early mobilization is an effective intervention to improve intestinal peristalsis in patients after cesarean section.